Enterprise performance management done right : an operating system for your organization - Dimon, Ron, 1963- (Wiley CIO., 2013)
A workable blueprint for developing and implementing performance management in order to improve revenue growth and profit margins Enterprise performance management (EPM) technology has been rapidly advancing, especially in the areas of predictive analysis and cloud-based solutions. Real Enterprise Performance Management introduces a framework for implementing and managing next-generation functionality for better insight, focus, and alignment of EPM. This blueprint shows that EPM can have a direct positive impact on revenue growth, operating margin, asset utilization, and cash c.